Effectiveness of aloe vera–menthol combination gel in reducing breast engorgement and pain among postpartum mothers: A Quasi-Experimental Study - Yoga Tri Wijayanti; Martini Martini; Yulyuswarni Yulyuswarni (Jurnal Ilmiah Kesehatan Sandi Husada, 2026)
Introduction: Breast engorgement is a common postpartum complication that contributes to maternal discomfort and early discontinuation of breastfeeding. Effective, accessible, and non-pharmacological management strategies are needed to support maternal and child health outcomes. Objective: To determine the effectiveness of a topical aloe vera–menthol combination gel in reducing breast engorgement severity and pain intensity among postpartum mothers. Research Methodology: A quantitative quasi-experimental study with a posttest-only control group design was conducted among 32 postpartum mothers experiencing breast engorgement in the working area of the East Lampung District Health Office, Indonesia. Participants were allocated into an intervention group (n=16) receiving aloe vera–menthol gel twice daily for four days and a control group (n=16) receiving standard breast care. Breast engorgement severity was measured using the Six-Point Engorgement Scale (SPES), and pain intensity was assessed using the Numeric Rating Scale (NRS). Data were analyzed using the Mann–Whitney U test and multivariable linear regression (α=0.05). Results: The intervention group demonstrated significantly lower SPES and NRS scores compared with the control group (p<0.001). After adjustment for age, parity, and breastfeeding frequency, the gel remained an independent predictor of reduced engorgement severity (β = -1.49; 95% CI: -2.05 to -0.93) and pain intensity (β = -2.21; 95% CI: -3.01 to -1.41). Conclusion: The aloe vera–menthol gel is an effective complementary topical therapy for reducing breast engorgement and pain in postpartum mothers and may support breastfeeding continuity in primary healthcare settings.